Pengaruh Budaya Organisasi Terhadap Keberhasilan Penerapan Prinsip-Prinsip Good Governance Dan Implikasinya Terhadap Kinerja Tenaga Kependidikan - Seto Wahyu Anggara; Edy Suwasono (Otonomi, 2023)
Based on the formulation of the problem, the objectives of this study are: 1) To analyze the influence of Organizational Culture on the successful Implementation of Good Governance Principles, 2) to analyze the influence of Organizational Culture on the Performance of Education Personnel at the AUAK Bureau of IAIN Kediri, 3) to analyze the influence of Organizational Culture indirectly on the Performance of Education Personnel at the AUAK Bureau of IAIN Kediri through the intervening variable Good Governance. The research time began on July 1, 2023 to August 31, 2023 or for 2 months. While the research location at the Bureau of AUAK IAIN Kediri. This research is explanatory research, which is research that aims to find the influence of the independent variable to the dependent variables. This research uses a quantitative approach with the research method, namely survey. All 32 members of the population were used as research samples. Data collection using questionnaires and data from paper and electronic documents. Based on the research results, it is concluded: 1) Organizational Culture affects the successful implementation of the Principles of Good Governance, 2) Organizational Culture affects the Performance of Education Personnel at the AUAK Bureau of IAIN Kediri, 3) Organizational Culture indirectly affects the Performance of Education Personnel at the AUAK Bureau of IAIN Kediri through the intervening variable Good Governance.